ANALISIS YURIDIS RUANG TERBUKA HIJAU TERHADAP PENCEGAHAN BANJIR DI SEBAGIAN JAKARTA BARAT - Nadya Rahma Putri; Hasni (Faculty of Law, Universitas Trisakti, 2023)
Public and private green open space are the two categories that make up green open space. The 2007 Law on Spatial Planning Number 26 regulates the percentage of green open space that urban areas must own. How can efforts be made to obtain at least 30% green open space in the West Jakarta region and how is the availability of public green open space for flood prevention in some areas of West Jakarta formulated as the problem? Utilizing normative and descriptive analysis techniques on two types of data-namely, secondary and primary data-in this study. Additionally, the analysis was conducted utilizing qualitative techniques, and results were reached using deductive reasoning. The findings of the study Discussion explain that the West Jakarta region's green open spaces still fall below the recommended minimum of 30%, making it impossible for them to effectively and efficiently serve as water catchment areas to prevent flooding in some regions of West Jakarta. The amount of green open space in West Jakarta is currently 8.64%, which is far below the existing target of at least 30%. As a result, green open space cannot currently prevent flooding in some areas of West Jakarta, and the Regional Government is making efforts to achieve the minimum target of 30% green open space, including land acquisition.